Spacecraft Anti‐Unwinding Attitude Control Using Second‐Order Sliding Mode. Issue 1 (25th August 2017) - Tiwari, Pyare Mohan; Janardhanan, S.; un‐Nabi, Mashuq
Abstract: This paper presents an anti‐unwinding control method for the attitude stabilization of a rigid spacecraft. Quaternion has double stable equilibrium and this may cause unwinding problems in spacecraft attitude control if both the equilibria are not considered in control design. Here, the initial condition of scalar quaternion is included in sliding surface and an anti‐unwinding control method is formulated in second‐order sliding mode. The presented second‐order sliding mode controller can alleviate chattering and ensure a smooth control for actuator. Further, to eliminate the need of advance information about bounds of uncertainty and external disturbance, adaptive laws are applied to estimate the controller gains. The closed‐loop stability is proved using the Lyapunov stability theory. In conclusion, a simulation is conducted in the presence of inertia uncertainty and external disturbances and it is found that the presented control method is efficient to negate the effect of inertia uncertainty and external disturbances, alleviate chattering, eliminate unwinding, and ensure high accuracy and steady state precision.